2010
DOI: 10.1111/j.1462-2920.2010.02285.x
|View full text |Cite
|
Sign up to set email alerts
|

Singlet oxygen, a neglected but important environmental factor: short‐term and long‐term effects on bacterioplankton composition in a humic lake

Abstract: Photolysis of dissolved organic matter (DOM) leads to contrasting effects on bacterioplankton dynamics, i.e. stimulation and inhibition of bacterial activity. In particular, the role of short-lived reactive oxygen species (ROS), e.g. singlet oxygen (¹O₂), in altering microbial activity and species composition has scarcely been investigated. Therefore, we have artificially increased the natural rate of ¹O₂ formation in short-term (∼4 h) in situ and long-term (72 h) laboratory incubations of surface water sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 82 publications
2
54
0
Order By: Relevance
“…3). Because shifts in bacterial community composition are related to the degree of change in bacterial substrates (29), these results support the idea that photobleaching and quantum yield of stimulated bacterial production are proxies for total photochemical transformations of DOM; increased photo-transformation alters DOM chemistry relative to the dark control, which in turn drives and supports shifts in bacterial species and activity. This result also suggests that natural bacterial communities in thermokarstdisturbed waters have the genetic and metabolic capacity to process deep soil C when it is exposed to surface conditions.…”
Section: Resultssupporting
confidence: 67%
“…3). Because shifts in bacterial community composition are related to the degree of change in bacterial substrates (29), these results support the idea that photobleaching and quantum yield of stimulated bacterial production are proxies for total photochemical transformations of DOM; increased photo-transformation alters DOM chemistry relative to the dark control, which in turn drives and supports shifts in bacterial species and activity. This result also suggests that natural bacterial communities in thermokarstdisturbed waters have the genetic and metabolic capacity to process deep soil C when it is exposed to surface conditions.…”
Section: Resultssupporting
confidence: 67%
“…This was not surprising considering that 1 O 2 exists in aquatic and terrestrial environments, where it is generated by photosensitizing humic substances (Frimmel et al, 1987; Steinberg et al, 2008), which are known to affect microbial populations including phytoplankton (Glaeser et al, 2010, 2014). Assuming that some of these transporters function to export photosensitizing molecules from the cell, our results suggest that removal of photosensitizers is an integral part of the 1 O 2 response in Chlamydomonas , rather than simply a response to the presence of a xenobiotic compound such as RB (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Febria et al (2006) found that the production of hydrogen peroxide (H 2 O 2 ) in two delta lakes that were also sampled herein (CON and TK) outpaced the rate of removal during a period of uninterrupted sunshine in 2004, leading to an accumulation of H 2 O 2 within the water columns. Production of ROS during previous studies of DOM photodegradation has been observed to inhibit community-level rates of carbon production (Scully et al 2003;Anesio et al 2005;Glaeser et al 2014) and result in changes in bacterial community composition (Glaeser et al 2010(Glaeser et al , 2014. Further, in a prior study by Lund and Hongve (1994), declines in BA of up to 60% were observed after only an hour when UV-irradiated DOM was mixed with bacteria.…”
Section: Photoreactivity Of Mackenzie River Freshet Dommentioning
confidence: 96%
“…To some extent, therefore, irradiation of DOM by sunlight simultaneously stimulates and inhibits heterotrophic bacterial production (BP) (Scully et al 2003;Ruiz-Gonzalez et al 2013), leading to complex interactions that can result in enhanced, negative, mixed, or no effect on bacterial community metabolism (Lonborg et al 2016). In addition, the bacterial community composition may be altered either by exposure to ROS (Glaeser et al 2010;Glaeser et al 2014) or in response to the increased lability of the pool of DOM substrate (Judd et al 2007;Piccini et al 2009;Paul et al 2012;Ward et al 2017), giving rise to a species assemblage that is better suited to the ambient conditions.…”
Section: Introductionmentioning
confidence: 99%